Phil Thornton talks about the background to the Challenge Program CCAFS - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
CCAFS is driven by the need for research and other communities to work together globally for the first time. Interview with Phil Thornton (CCAFS/ILRI). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya